COMMON FIXED POINT THEOREMS FOR SOME CONTRACTIVE CONDITION WITH φ-MAPPING IN COMPLEX VALUED B-METRIC SPACES - Inchan, I.; Gajai, K.; Yuying, T.; Youyen, S.; Chantakun, W. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2021)
In this paper, by using the concept of -mappings introduced by Mohanta and Maitra [8], we can prove the existence and the uniqueness of common fixed points for some generalized contractive mappings in complex-valued b-metric spaces. Our results extend and improve the results of Tripathi and Dubey [12] and many others.